1996
DOI: 10.1038/icb.1996.7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the recombinase‐activating gene (RAG‐1) in murine early embryogenesis

Abstract: Summary The recombinase activation genes, RAG‐1 and RAG‐2, are expressed together in immature T or B lymphocytes and possess activity to induce V(D)J rearrangement in T cell receptor (TCR) and Ig genes. In vertebrates, only Ig and TCR molecules are reported to have recombination in their development using multiple V, D, J component gene segments. Thus, expression of RAG genes are localized only in lymphoid organs and sites of extrathymic T cell differentiation. In this study, we have used RAG‐1 and RAG‐2 genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…PCR entailed initial denaturation at 94°C for 12 minutes, followed by 50 cycles of 94°C for 1 minute, 58°C for 2 minutes, 72°C for 3 minutes, with final extension at 72°C for 7 minutes. RT-PCR cycles for Tg and ␤ actin were performed as described (7,9). RT-PCR products (10 L) were separated by electrophoresis on a 2.0% agarose gel.…”
Section: Rt-pcrmentioning
confidence: 99%
“…PCR entailed initial denaturation at 94°C for 12 minutes, followed by 50 cycles of 94°C for 1 minute, 58°C for 2 minutes, 72°C for 3 minutes, with final extension at 72°C for 7 minutes. RT-PCR cycles for Tg and ␤ actin were performed as described (7,9). RT-PCR products (10 L) were separated by electrophoresis on a 2.0% agarose gel.…”
Section: Rt-pcrmentioning
confidence: 99%
“…In humans, an intriguing observation is that the CD56 bright+ /CD16 - cells, numerous at early pregnancy, drastically drop at the second and third trimester and are practically absent at term. Moreover, they express c-kit and the recombinase activating genes (RAG) 1 and RAG2, suggesting TCR rearrangement processes or/and a progenitor nature of these cells [13,17,18]. …”
Section: The Leukocyte Population At the Feto-maternal Interface – Dementioning
confidence: 99%
“…In previous reports, Hayakawa et al [17] in the human system and Kimura et al [18] in the murine system have shown expression of mRNA for RAG-1 and RAG-2 proteins, which are required for TCR rearrangement, in human CD56 bright /CD16 - cells and in murine decidual mononuclear cells respectively. We have confirmed and extended these results showing that transcripts of RAG can be easily detected in purified CD56 + , CD2 + , c-kit + or IL-7R + decidual cells implying an ongoing process of TCR gene rearrangement [13].…”
Section: γδT Cells In Pregnancymentioning
confidence: 99%
“…The recombinase complex is tightly regulated at tissue, cellular and molecular levels. First, RAG1 and 2 are both expressed only in lymphocytes, though one or the other are expressed at low levels in different non-lymphoid tissues (1921). Second, RAG expression is downregulated throughout the G1/S phase of the cell cycle and during the cell divisions following the recombination of an antigen receptor locus (22, 23), which occur primarily after the production of a functional heavy chain of antigen receptor (TCRβ, TCRδ, and IgH loci) and secondly after the expression and the pairing of the light chain to the heavy chain (TCRα, TCRγ, and Igλ or Igκ, respectively) to form the cell surface receptor.…”
Section: Introductionmentioning
confidence: 99%